Efficiency, Weak Value Maximality and Weak Value Optimality in a Multisector Model - Mitra, Tapan (Review of Economic Studies, 1981)
Journal Article Efficiency, Weak Value Maximality and Weak Value Optimality in a Multisector Model Get access Tapan Mitra Tapan Mitra State University of New York, Stony Brook Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 4, October 1981, Pages 643–647, https://doi.org/10.2307/2297203 Published: 01 October 1981 Article history Received: 01 March 1977 Accepted: 01 October 1980 Published: 01 October 1981